Laser cladding composite coatings by Ni–Cr–Ti–B4C with different process parameters. Issue 8 (11th June 2019) - Han, Tengfei; Xiao, Meng; Zhang, Ying; Shen, Yifu
ABSTRACT: To investigate the effect of laser process parameters on microstructure and properties of composite coating, the composite coatings were manufactured by laser cladding Ni–Cr–Ti–B4 C mixed powder on Q235 mild steel with different process parameters. The coatings are bonded with the substrate by remarkable metallurgical binding without cracks and pores. The composite coatings are consisted of in situ synthesized solid solution Ni–Cr–Fe, intermetallic compound (IMC) Ni3 Ti, Cr2 Ti, and ceramic reinforcements TiB2, TiC. Results of scanning electron microscopy (SEM) revealed that the ceramic reinforcements became coarser with higher specific energy ( E s ). There were independent ceramics TiB2, TiC, eutectic ceramic TiB2 –TiC in coatings, and eutectic alloy–ceramic was detected. Compared with the substrate, the microhardness of coatings was increased significantly, and the maximum microhardness of coatings was approximately five times as high as the substrate. The wear resistance of coatings was improved dramatically than the substrate. Compared to the coatings with lower E s, higher E s led to lower microhardness and worse wear resistance ascribing to more Fe diffused into the coating from the substrate.